Analysis of Elasticity and Sugar Content In Traditional Wajik Sasak Snack Menu - Lalu Usman Ali; Muzzazinah (Kappa Journal, 2024)
The purpose of this study was to determine the value of the modulus of elasticity and sugar content in Wajik snacks. Wajik is one of the traditional snacks that is popular with many people. The sweet and legit taste of wajik increases consumer interest in this product. This product is a semi-wet food made from glutinous rice, coconut milk and brown sugar. Coconut milk is a mandatory additional ingredient in making wajik, because the oil produced by coconut milk will produce a legit and savory taste. Coconut milk also produces fat in wajik. Elasticity was analyzed from 5 samples of wajik snacks and Analysis of sugar content (fructose, glucose, sucrose) was carried out using the high performance liquid chromatography (HPLC) method and total calorie analysis was carried out by adding calories from protein, fat, carbohydrate components or by calculation method. Protein content was analyzed using the Kjeldahl method, total fat analysis was carried out using the Weibull method, total carbohydrates were determined using the by difference method.